Signalisieren und Screening in Arbeitsmärkten - die Experimente von Brandts & Holt und Kübler et. al - Kaiser, Sarah

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

Collective action and the common enemy effect - De Jaegher, Kris; Hoyer, Britta (Defence and Peace Economics)
How is collective defence by players affected when they face a threat from an intelligent attacker rather than a natural threat? This paper analyses this question using a game-theoretic model. Facing an intelligent attacker has an effect if players move first and visibly set their defence strategies, thereby exposing any players who do not defend, and if the attacker is, moreover, not able to commit to a random attack. Depending on the parameters of the game, the presence of an intelligent attacker either increases the probability that players jointly defend (where such joint defence either does or does not constitute a utilitarian optimum), or decreases the probability that players jointly defend (even though joint defence is a utilitarian optimum).

On the Relation between Innovation and Competion: The Case of Energy Industry - Brummel, NinaMadeleine

Horizontale Fusionen: Theorie und Praxis am Beispiel zweier Entscheidungen des Bundeskartellamtes - Eusterholz, Fabian

Die ökonomischen Auswirkungen der Kronzeugenregelung am Beispiel des Kaffeerösterkartells - Wemhöner, Vanessa

Network Disruption and the Common Enemy Effect - Hoyer, Britta; De Jaegher, Kris
The phenomenon that groups or people work together when they face an opponent, although they have little in common otherwise, has been termed the "common enemy effect". We study a model of network formation, where players can use links to build a network, knowing that they are facing a common enemy who can disrupt the links within the network, and whose goal it is to minimize the sum of the benefits of the network. We find that introducing a common enemy can lead to the formation of stable and efficient networks as well as fragmented networks and the empty network.

Paying for Performance in Hospitals - Hehenkamp, Burkhard; Kaarboe, Oddvar (Economic Analysis and Policy)

Survival at the center—the stability of minimum differentiation - Hehenkamp, Burkhard; Wambach, Achim (Journal of Economic Behavior & Organization)

On the equivalence of Nash and evolutionary equilibrium in finite populations - Hehenkamp, Burkhard; Possajennikov, Alex; Guse, Tobias (Journal of Economic Behavior & Organization)